2021
DOI: 10.1097/mph.0000000000002187
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of an Immunogenic Response to Pneumococcal Vaccination in Children With Sickle Cell Disease

Abstract: Patients with sickle cell disease (SCD) are at increased risk for invasive pneumococcal disease because of splenic dysfunction. To mitigate this risk, patients are protected with prophylactic penicillin until completion of pneumococcal vaccination series. The objective of this study was to assess the maintenance of a protective immune response to pneumococcal vaccination in children with SCD. A retrospective review was conducted between June 2019 and June 2020 of all patients with SCD patients for whom it had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Yee et al demonstrated in a 10-year cohort analysis that there was a significant decline in bloodstream infections due to pneumococcal vaccination in addition to lowering IPD [ 23 ]. Other studies also showed that almost 70% of patients with SCD maintained immunogenicity to IPD for up to five years following vaccination [ 30 , 31 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yee et al demonstrated in a 10-year cohort analysis that there was a significant decline in bloodstream infections due to pneumococcal vaccination in addition to lowering IPD [ 23 ]. Other studies also showed that almost 70% of patients with SCD maintained immunogenicity to IPD for up to five years following vaccination [ 30 , 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, although there is overwhelming evidence for the role of vaccination in reducing the incidence of IPD in patients with SCD, the currently available vaccines do not cover up to 60% of serotypes that cause infection in SCD patients [ 30 ]. This is because pneumococcal serotypes constantly change in virulence, dependent on age, region, socioeconomic status, etc.…”
Section: Reviewmentioning
confidence: 99%